PERANAN MAHASISWA KULIAH KERJA NYATA (KKN) DALAM PENGUATAN LITERASI SISWA SD KELURAHAN PANCURAN DEWA SIBOLGA - Sahara, Nur; Ginting, Nurmaini; Harahap, Fatma Suryani; Mariska, Revi; Amanda, Dea; Damayanti, Dina (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The point of this exploration is to give an outline of the incorporation of worksheets with regular signs of corrosive base learning results, as well as the impact on gaining results and understudy discipline from this combination. This study employs a single group design, which means it is conducted in a single class. The data were collected using student discipline observation sheets, pretest and posttest observation sheets, and observation sheets. According to the findings of this study, the medium category has a N-Gain percentage of 56.10 percent, while the very good category has an average learning completion score of 100 and pre-test scores of 46.1 and 81, respectively. %. execution perceptions. In the mean time, for understudy discipline, the typical accomplishment was 89.53 percent, which is named generally excellent. It is possible to draw the conclusion, based on the findings of this study, that incorporating natural indicators of acid base learning into worksheets for students is quite effective at encouraging discipline in learning and improving student learning outcomes